Teaching Indonesian-English Combined Task to Improve Students’ Skills in Writing English Sentences - Muhajirah Idman; Mustaqimah Mustaqimah (LETS: Journal of Linguistics and English Teaching Studies, 2021)
This research aimed to find out the effectiveness of Teaching Indonesian-English Combined Task to improve students’ skills in writing English sentences. It was undertaken in PDF Ulya As’adiyah Putri Sengkang in Academic Year 2016/2017. It applied pre-experimental method. Writing test was employed as the instrument of the research. The population of this research was 16 students. The technique of data collection involved giving pre-test to know the writing skills gained previously of the students and post-test after giving the treatment to know how the skills of the students in writing English sentences by using Indonesian-English combined task. The result of the calculation of the students’ score indicated that the mean score of the students’ pre-test was (55.25) which was classified as fair classification and the mean score of the students’ post-test was (73,93) as good classification. The value of paired sample test for post-test was greater than the t-table. In short, teaching Indonesian-English combined task is effective to improve students’ skills in writing English sentences.